The Risk Implications of ESG Performance : An Empirical Analysis of Norwegian Listed Companies (2014 - 2023) - Piironen, Jeremi (My University, 2025)
This thesis examines how companies' ESG (Environmental, Social, Governance) scores are reflected in the equity risk of Norwegian listed companies between 2014 and 2023. The study focuses on risk, which is measured by two indicators: the annual volatility of the stock price and systematic risk (beta). The empirical data consists of firm-level observations and annually formed ESG portfolios. The methodology is based on linear regression models used to analyze the relationship between overall ESG scores, individual ESG dimensions (E, S, and G), and risk measures. The results show that higher ESG scores are consistently associated with lower volatility, and this association remains statistically significant even after controlling for firm size and beta. Among the ESG components, the environmental dimension exhibits the strongest negative association with volatility. In contrast, the association with systematic risk (beta) is positive but weak, and not statistically significant in most models. The portfolio analysis confirms the firm-level findings: companies with low ESG scores display higher average volatility than those with a high ESG level. The findings support the view that a strong ESG profile can function as a risk management tool by reducing firm-specific, idiosyncratic risk. At the same time, ESG does not appear to serve as a hedge against systematic market risk. The results are consistent with prior literature suggesting that ESG performance conveys meaningful risk-relevant information to investors.

Tässä tutkielmassa tarkastellaan, kuinka yritysten ESG-pisteytys (Environmental, Social, Governance) heijastuu norjalaisten pörssiyhtiöiden osakeriskiin vuosina 2014–2023. Tutkimuk-sen näkökulma keskittyy riskiin, jota mitataan kahdella indikaattorilla: osakekurssin vuotuisella volatiliteetilla sekä systemaattisella riskillä (beta). Empiirinen aineisto koostuu yritystason tiedoista ja vuosittain muodostetuista ESG-portfolioista. Menetelmänä käytetään lineaarisia regressiomalleja, joilla analysoidaan ESG:n kokonaispisteiden ja yksittäisten osa-alueiden (E, S ja G) yhteyttä riskimuuttujiin. Tulokset osoittavat, että korkea ESG-pisteytys on johdonmukaisesti yhteydessä matalampaan volatiliteettiin, ja tämä yhteys säilyy tilastollisesti merkitsevänä myös kontrollimuuttujien, kuten yrityskoon ja betan, lisäämisen jälkeen. Erityisesti ympäristöulottuvuudella havaittiin vahvin negatiivinen yhteys riskiin. Sen sijaan yhteys systemaattiseen riskiin (betaan) oli positiivinen mutta heikko, eikä se ollut tilastollisesti merkitsevä useimmissa malleissa. Portfolioanalyysi vahvisti yritystason havainnot: matalan ESG-tason yhtiöillä oli keskimäärin korkeampi volatiliteetti kuin korkean ESG-tason yhtiöillä.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance